Effects of Purified Bauhinia Variegate Leaves and Methanolic Extract on Diabetic Type-2 Alloxan-Induced in Male Albino Rats - Jameelah Kadhim Taher (Journal of Global Pharma Technology, 2018)
The anti-diabetic effects of purified Bauhinia variegate leaves and methanolic extract were Compared with standard drug Insulin. In vivo studyreveals that animal treated with methanolic extract of Bauhinia variegate show reduction in blood glucose sigificantly, body weight, triglycerides, HDL, cholesterol in Alloxan induced diabetic rats. In Bauhinia variegate treated group, there are no significant increase in urea and creatinine level when compared to the control group which reveals the protective nature of the plant source. It concludes that In vivo antidiabetic activity of whole plant extracts of Bauhinia variegate on normal and Alloxan induced diabetic rats was evaluated and concluded that it possesses anti-diabetic activity. From the above results, it is conducted that purified leaves and methanolic extract of Bauhinia variegate whole plant possess significant hypoglycemic and hypolipidemic effects in alloxan induced diabetic rats.Keywords: Bauhinia variegates, Hypoglycemic, Hypolipidemic, Methanilic extract.